General practitioner and mental healthcare use in a community sample of people with diagnostic threshold symptoms of bulimia nervosa, binge‐eating disorder, and other eating disorders. Issue 1 (8th October 2019) - Hay, Phillipa; Ghabrial, Brittany; Mannan, Haider; Conti, Janet; Gonzalez‐Chica, David; Stocks, Nigel; Heriseanu, Andreea; Touyz, Stephen
Abstract: Objective: Lengthy delays in receiving treatment have been reported for people with bulimia nervosa (BN) and binge‐eating disorder (BED). This study aimed to investigate healthcare use and predictors of mental health specialist healthcare use in a community sample of individuals with diagnostic threshold symptoms of BN, BED‐Broad, or another eating disorder (Other ED). Method: In 2017, 2, 977 individuals aged ≥15 years were interviewed in a general population survey. Participants were asked questions relating to sociodemographic, ED symptoms, other clinical features, and healthcare use data. Assessment of ED symptoms was based on diagnostic questions derived from the eating disorder examination. Results: Thirty‐six participants with symptoms of BN, 33 participants with BED‐Broad, and 369 with an Other ED were identified. Fewer people with symptoms of BN/BED‐Broad (23%) or an Other ED (6%) had treatment from a mental health specialist than from a general practitioner (GP; 80%, 71.6%). Healthcare use differed significantly across type of ED only for treatment from a mental health specialist. In multivariate analyses, being asked about a person's mental health by a GP was the best explanatory variable for receiving treatment from a mental health specialist. Discussion: A large treatment gap exists in healthcare for people with EDs. Inquiry about an individual's mental health by a GP was associated with higher rates of treatment from mental health specialists. However, a similar diet/eating inquiry did not have this association. Future research should consider the use of this patient and practitioner consultation in targeting improved detection of EDs.